Feasibility Study of a Modified XELOX Adjuvant Chemotherapy for High-Recurrence Risk Patients With Operated Stage III Colon Cancer - Peng, Jianhong; Li, Weihao; Fan, Wenhua; Zhou, Wenhao; Zhu, Ying; Li, Xueying; Pan, Zhizhong; Lin, Xiaoping; Lin, Junzhong (Frontiers in Pharmacology, 2020)
Background: Our previous study reported the favorable efficacy and good tolerance associated with a modified XELOX adjuvant chemotherapy with 8 cycles of capecitabine and 6 cycles of oxaliplatin for operated stage III colon cancer. The current study aimed to confirm the feasibility of modified XELOX chemotherapy for treating specific high-risk (T4, N2, or both) stage III colon cancer. Methods:We selected 142 consecutive patients with high-risk stage III colon cancer who received colon tumor resection followed by modified XELOX or standard full-cycle XELOX chemotherapy from November 2007 to June 2016 at Sun Yat-sen University Cancer Center. Disease-free survival (DFS), overall survival (OS), and adverse events of patients treated with the two chemotherapy regimens were compared. Results: Seventy-four (52.1%) patients received standard XELOX chemotherapy, and 68 (47.8%) received modified XELOX chemotherapy. Neurotoxicity was the most common adverse event in 99 (69.7%) patients. Grade 2-3 neurotoxicity, grade 2-4 thrombocytopenia and grade 3-4 leucopenia were the major severe adverse events related to the decision to treat patients with modified XELOX chemotherapy. After a median follow-up of 69 months, the modified XELOX group presented a comparable 5-year DFS rate (79.0 vs 80.3%, P = 0.891) and 5-year OS rate (93.8% vs 87.8%, P = 0.446) as those in the standard XELOX group. Univariate survival analysis indicated that poor tumor differentiation (HR: 2.381, 95% CI: 1.141-4.968, P = 0.021) was the only significant risk factor for DFS, but no significant prognostic factor was identified for OS. Conclusions: The modified XELOX adjuvant chemotherapy presented a comparable oncologic efficacy as standard XELOX chemotherapy for high-risk stage III colon cancer. The modified XELOX adjuvant chemotherapy could be an alternative treatment for patients suffering severe adverse events, especially severe neurotoxicity.